2003
DOI: 10.1074/jbc.m310166200
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Treatment with Interleukin-1β Attenuates Contractions by Decreasing the Activities of CPI-17 and MYPT-1 in Intestinal Smooth Muscle

Abstract: Interleukin-1␤ (IL-1␤) is a proinflammatory cytokine that plays a central role in inflammatory bowel disease (IBD). In order to elucidate the mechanism of motility disorders frequently observed in IBD, we investigated the long term effects of IL-1␤ on rat ileal smooth muscle contractility by using an organ culture system. When ileal smooth muscle strips were cultured with IL-1␤ (10 ng/ml), contractions elicited by high K ؉ and carbachol were inhibited in a time-dependent manner. IL-1␤ more strongly inhibited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
113
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(125 citation statements)
references
References 61 publications
12
113
0
Order By: Relevance
“…Sato et al (48), however, reported hypocontractility of mouse colonic circular smooth muscle obtained from DSS-treated colon that was mediated by a decrease in CPI-17 expression. Their findings are similar to those previously by others and us in circular smooth muscle exposed to IL-1␤ or obtained from TNBS-treated colon (16,43,52). Shi and co-workers (52) have reported that decrease in circular muscle contraction obtained from DSS-treated rat colon was due to suppression of G␣ q protein, whereas in TNBS-treated rat colon was due to suppression of ␣ 1c 1b subunit of Ca v 1.2 b channels, G␣ q and CPI-17.…”
Section: Discussionsupporting
confidence: 81%
“…Sato et al (48), however, reported hypocontractility of mouse colonic circular smooth muscle obtained from DSS-treated colon that was mediated by a decrease in CPI-17 expression. Their findings are similar to those previously by others and us in circular smooth muscle exposed to IL-1␤ or obtained from TNBS-treated colon (16,43,52). Shi and co-workers (52) have reported that decrease in circular muscle contraction obtained from DSS-treated rat colon was due to suppression of G␣ q protein, whereas in TNBS-treated rat colon was due to suppression of ␣ 1c 1b subunit of Ca v 1.2 b channels, G␣ q and CPI-17.…”
Section: Discussionsupporting
confidence: 81%
“…We previously reported that ROCKs and PKC phosphorylate CPI-17 at Thr38 in the rat small intestine [20]. We therefore examined the effects of 17-estradiol on carbachol-induced phosphorylation of CPI-17 in organ-cultured ileal tissues (Fig.…”
Section: -Estradiol Downregulates Phosphorylation Of Cpi-17 At Thrmentioning
confidence: 99%
“…Organ culture was performed as described previously [19,20]. Ileal tissues were isolated from the distal ileal region of Wistar rats (age, 7 weeks; male) and the circular ileal smooth muscle layer was carefully separated from the mucosal layer.…”
Section: Organ-cultured Circular Ileal Smooth Muscle Tissuesmentioning
confidence: 99%
See 2 more Smart Citations